Determination and evaluation of the pyridoxal, pyridoxine, and pyridoxamine forms of vitamin B6 in plant-based foods in terms of healthy vegetarian nutrition: Vitamin B6 profile in plant baded foods - Koseoglu, Sabiha Zeynep Aydenk (Progress in Nutrition, 2020)
Background and Objective: Vitamin B6 deficiency is observed in vegetarians. In many studies, vitamin B6 is determined as the sum of the pyridoxal (PL), pyridoxine (PN) and pyridoxamine (PM) forms. Because the bioavailability of the PL, PN and PM forms of vitamin B6 are different, knowing the amounts of these forms in foods is important for healthy nutrition. The aim of this study was to determine the PL, PN and PM forms of vitamin B6 in plant-derived foods and to evaluate these forms in terms of vegetarian and nonvegetarian nutrition. Methodology: In this study, a total of 61 foods from the vegetable (26), fruit (19), grain (10), legume (3) and nut (3) categories were examined using high-performance liquid chromatography (HPLC). Results: It was found that vegetables, fruits and grains contained more of the PN form along with the PL and PM forms, while the PL form was found in high levels in nuts. The PL form was found at an average rate of 29.6% in vegetables and 19.4% in fruits. The PN form was found predominantly in legumes and grains. Conclusions: When we evaluated the results, vegetables, fruits and grains contained more of the PN form along with the PL and PM forms, while the PL form was found in high amounts in nuts. Many vegetables contain low amounts of protein, but they contain high amounts of vitamin B6 in the PLP form. These foods can be consumed together with foods that contain high levels of protein (legumes, grains) and low levels of vitamin B6 in the context of vegetarian nutrition. This profile determination study will be an important source of information for the planning of various healthy diets for vegetarians as well as nonvegetarians.